Circular Economy as an Important Subject of Environmental Education in the Era of Energy Demand - Kluczkowski, Andrzej; Wyrostkiewicz, Michał (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
Civilization development has led to many facilities in human life and business, but has also introduced major changes and created a new order that over time has come to be in opposition to nature. The opportunity to reconcile ecological, economic and social reasons is to be found in the idea of sustainable development. The prerequisite for achieving sustainable development is education, which is one of the fundamental human rights that enables integral development. The purpose of the study was to verify the role and importance of education in the emergence and implementation of a circular economy idea. As it turned out, research has shown that sustainable development is largely dependent on the implementation of the circular economy, in which, the education is a fundamental and necessary tool